Tear Gas Ammunition and Gunshot Residues - Üner, Hüseyin Bülent; Şam, Bülent; Kurtaş, Ömer; Atasoy, Cüneyt; Uysal, Cafer (The Bulletin of Legal Medicine, 1997)
Tear gas (CS and CN) is an irritant and produces lacrimation and irritation of skin and respiratory tract. In this study information about tear gas ammunition is given. Test shots were fired on white cotton cloth using a Valtro semiautomatic pistol with 8mm CS and CN tear gas ammunition. Shooters fired the weapon with white cloth gloves. Gunshot residues on shoooters hands and targets were analysed. Key Words: Tear gas, chlorobenzylidenemolononitrile, Chloroacetophenone, Starter’s pistol, Gunshot residues.